Descriptive cognates of Tagalog, Iloko, Pangasinan and Kapangpangan - Nartea, Remedios Valenton 1934-
This paper analyzed the deceptive cognates of Tagalog, Iloko, Pangasinan, and Kapampangan. The contrastive study used the criteria of form, meaning, and distribution. It was revealed that languages differ in their vocabularies to a varying degree; some words can be cognates and deceptive cognates of two languages at the same time. Thru affixation, some words can change the form class to which they belong. Neighboring areas have less deceptive cognates than non-neighboring areas.